2009
DOI: 10.1021/es803287v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coating of Dicarboxylic Acids on the Mass−Mobility Relationship of Soot Particles

Abstract: Atandem differential mobility analyzer (TDMA) and a differential mobility analyzer-aerosol particle mass analyzer (DMA-APM) have been employed to study morphology and hygroscopicity of soot aerosol internally mixed with dicarboxylic acids. The effective densities, fractal dimensions, and dynamic shape factors of soot particles before and after coating with succinic and glutaric acids are determined. Coating of soot with succinic acid results in a significant increase in the particle mobility diameter, mass, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
115
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 34 publications
16
115
0
Order By: Relevance
“…The APM is located upstream of the SMPS for improved time resolution (∼1 min) over the more common configuration of the differential mobility analyzer (DMA)-APM (McMurry et al 2002;Khalizov et al 2009;Xue et al 2009). A detailed description of the APM-SMPS system and data algorithms are described elsewhere (Malloy et al 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The APM is located upstream of the SMPS for improved time resolution (∼1 min) over the more common configuration of the differential mobility analyzer (DMA)-APM (McMurry et al 2002;Khalizov et al 2009;Xue et al 2009). A detailed description of the APM-SMPS system and data algorithms are described elsewhere (Malloy et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the APM setting was programmed to select 3-5 different particle masses (typically in 20 min) to obtain particle density as a function of particle mass. Fractal-like dimension was obtained by fitting the effective density versus size relationship into a power function (Park et al 2003;Xue et al 2009): where ρ eff is the effective density of particles, C is a constant, d m is the mobility diameter of particles, and D f is the fractal-like dimension.…”
Section: Methodsmentioning
confidence: 99%
“…BC aging leads to a large variation in the particle morphology, depicted in the evolutions of the effective density (ρ eff ) and dynamic shape factor (DSF) ( , and 0.25 g·cm −3 and 2.2, 2.5, and 2.8, respectively, indicating fractal aggregates with chain-like branches (10,11,(20)(21)(22) and a more fractal morphology for a larger size. Our estimated fractal dimension of 2.25 for fresh BC particles is similar to those in the previous studies (13,22,23).…”
Section: Significancementioning
confidence: 99%
“…Zhang and colleagues (50,51) found that soot can reduce the photolysis frequencies of O 3 and NO 2 by absorbing sunlight, leading to a reduction in the concentration of HOx and O 3 . However, the optical properties of soot greatly depend upon its morphology, composition, and structure (21,22,52,53). Thus modification of soot during the photochemical aging process by O 2 may significantly alter its optical properties, resulting in changes in the effects of soot on the photochemistry of some atmospheric oxidants.…”
Section: −1mentioning
confidence: 99%